THE LIFE AND LEGACY OF ALEXANDER FAINBERG: A JOURNEY THROUGH THE POET'S LIFE VIA HIS CHARACTER AND ACHIEVEMENTS (Web of Teachers: Inderscience Research, 2025)
This article gives information about the life, character, and literary achievements of Alexander Feinberg, a prominent poet and translator, who became deeply connected to Uzbekistan. Feinberg's poetry is characterized by its philosophical depth, emotional resonance, and reflections on love, politics, and the human condition. The article also emphasizes Feinberg's impact on Uzbek and Russian literature, including his translation work and contributions to film. His approachable personality and lasting legacy as a poet are also discussed through personal anecdotes, providing a multifaceted view of his life and work.